A Novel Design Reconfigurable Antenna Based on the Metamaterial for Wearable Applications. Issue 1 (August 2021) - Gburi, Mohaimen Al; Ilyas, Muhammad
Abstract: A novel design of wearable antenna depending on metamaterials inspired-fractal Minkowski-shaped for industrial, scientific, and medical (ISM) applications is presented. The antenna consists of a conventional monopole and a Chebyshev transformer coupled with a unit cell of a fractal Minkowski curve to obtain three bands covering the ISM and Wireless Local Area Network (WLAN) applications. To enhance the antenna performance, the authors proposed the Electromagnetic Band Gap (EBG) layer of 3×4 array is introduced into the design structure. The authors used material FR4 dielectric as a substrate to design the antenna with dimensions of 51mm x 45mm x 1.6mm and fed by a 50 Ω port. The Antenna performance is analyzed numerically using CST Microwave Studio (CSTMWS) depending the Finite Integral Technique (FIT). Various investigation analyses have carried out to verify optimum antenna performance. The proposed antenna realizes reconfiguration by using the PIN diode. In both cases (switching= ON, OFF) the antenna achieves good bandwidth, |S11 |<-10dB, and excellent impedance matching.